Goals and satisfaction with life in Spanish and Peruvian adolescents according to sex and socioeconomic level - Díaz Morales, Juan Francisco (2004)
This study analyzes the kind of personal goals and life satisfaction levels amongst Spanish andPeruvian adolescents according to their sex and socioeconomic leve!. 389 Spanish and 285 Pe ruvian adolescents of both sexes from different socioeconomic leve! participated in this study. For the Spanish sample Palys and Little's (1983) Personal  Goals Analysis and Andrews and Withey's (1976) D-T Scale (Delight-Terrible) were used; for the Peruvian sample the measure ment instruments were Nuttin's (1985) Motivational lnduction Method along with Pavot and Diener's (1993) Life Satisfaction Scale. Results show significant similarities in the goals des cribed by both samples, as well as sex differences and socioeconomic differences.